Computed tomographic measurements of pancreatic thickness in clinically normal dogs - An, Yoojin; Kim, Sungsoo; Kwon, Danbee; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2023)
Pancreatic thickness is an indicator for evaluating pancreatic diseases. The transverse and cross-sectional pancreatic thickness observed on computed tomography (CT) may differ. This study aimed to provide a normal reference range for pancreatic thickness on the transverse plane based on body weight (BW) and assess pancreatic thickness to aorta (P/Ao) ratio. In addition, we aimed to establish the normal short and long dimensions of the pancreas based on cross-sectional image through the long axis of the pancreas using multiplanar reconstruction (MPR). The short dimension to aorta (S/Ao) and long dimension to aorta (L/Ao) ratios were also established in clinically normal dogs. The pancreatic thickness was measured using CT results of 205 clinically normal dogs. The pancreatic thickness on the transverse plane and the short and long dimensions in the cross-sectional image of the pancreas were measured using MPR. The diameter of the Ao was measured on the transverse plane and the P/Ao, S/Ao, and L/Ao ratios were calculated. Our study showed that the mean normal pancreatic thicknesses (mean ± standard deviation [SD]) of the pancreatic body, left and right lobe in the transverse plane were 10.92 ± 2.54 mm, 8.92 ± 2.26 mm and 9.96 ± 2.24 mm, respectively. The P/Ao ratios of the pancreatic body, left and right lobes were 1.85 ± 0.33, 1.50 ± 0.27 and 1.68 ± 0.29, respectively. The mean short dimension (mean ± SD) in the cross-sectional image of the pancreatic body, left and right lobe were 8.98 ± 1.97 mm, 7.99 ± 1.89 mm and 8.76 ± 2.03 mm, respectively. In conclusion, pancreatic thickness increased with BW, while the P/Ao, S/Ao, and L/Ao ratios could be used regardless of BW.